Microgrid multi-distributed energy resources for power management network stability / Bilal Mouneir Saeed Eid - Bilal Mouneir, Saeed Eid (2016)

(untitled)
The increased demand for power that has to be transferred over long distances within increasing load growth makes the integration of Distributed Energy Resources (DERs) a fast and effective solution. DERs are able to reduce the electrical and physical distances between load and generator, transmission and distribution power losses, and the carbon emission levels. They can also eliminate bottlenecks from distribution and transmission lines. DERs are able to improve reactive power to enhance grid voltage profile and power stability, and utilize waste heat better, postponing the necessity to establish new transmission lines and huge power generation plants. Increased penetration of DERs into conventional power systems, however, increases control challenges. Such challenges can be overcome by a microgrid, whose many features include integrating DERs without interrupting the grid operation, enabling power systems to observe and control faults more effectively, reducing the damage caused by DER outages, feeding critical loads continually, allowing load shedding and automated switching through control algorithms so outages and power restoration time are shortened, allowing either grid-connected or islanded operation, and improving system reliability and flexibility through DER’s many options. This work examines the structure of microgrids and reviews their classifications and the literatures discussing their control objectives. It finds that the use of microgrids enhances a conventional power system’s grid smartness. It summarizes microgrid control objectives and their most common problems and solutions. It also proposes a single-stage power converter for electronically coupled distributed generation; the converter is able to track the maximum power point and yield unity power factor. A model for the Photovoltaic (PV) array and three-phase grid-connected inverter shows the control parameters. The inverter’s controller uses inner and outer control loops to control the injected current and DC voltage. The inner control loop controlling the current by converting the input iii from the abc frame to the dq0 frame then yield the desired reactive power value. The outer voltage control loop tracks the maximum power point through a dynamic reference DC-voltage technique. The active power produced by the single-stage and double-stage power converters are compared (the single-stage converter showed higher efficiency). A dynamic reference voltage is proposed and the variable and the fixed DC reference voltages are compared for their active power yields in the proposed single-stage converter system. The impact on the active and reactive powers, by ambient disturbances such as solar radiation with severe disturbances, and variable PV cell temperature, are investigated. The active and reactive power flows and the voltages of the system at three distances of distribution line are investigated and verified by Matlab/Simulink. In low-voltage networks with a high penetration of Renewable Energy Sources (RESs), various disturbances may occur such as voltage fluctuation, frequency deviation, high reverse power flow, and high circulating reactive power. This work also proposes a largescale microgrid grid-connected system of PV and Fuel cell (FC) sources for improving the voltage profiles. Three microgrid configurations were tested using the proposed control strategy to determine the reactive power generated by RESs. The test conditions considered load disturbances, variations in solar radiation( in case one), feeder removal and partial shading (in case two). In other test conditions, we validated a voltage regulator implemented for an FC inverter. The voltage stability was improved at the load bus by maintaining the voltage within acceptable limits. All three microgrid configurations exhibited similar active power losses, but only one of the microgrid configurations had a rapid response time and low circulating reactive power. The results of this study demonstrate the effectiveness of connecting an FC source (i.e., the dispatchable source) to the load bus for regulating the voltage. The effectiveness and superior performance of the proposed configuration verified by comparison with other configurations using Matlab/ Simulink.